2014
DOI: 10.3109/00365521.2013.846404
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in high-risk patients with bleeding Mallory–Weiss syndrome is similar to that of peptic ulcer bleeding. Results of a prospective database study

Abstract: The incidence of bleeding Mallory-Weiss syndrome and peptic ulcer bleeding has not changed over a five-year observational period. The overall 30-day mortality was almost equal for both bleeding Mallory-Weiss syndrome and peptic ulcer bleeding and was positively correlated to older age and underlying comorbid illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 14 publications
2
23
0
1
Order By: Relevance
“… 41 , 42 A prospective study found that the 30-day mortality rate in Mallory-Weiss syndrome was 5.3%, similar to the mortality rate in peptic ulcer bleeding. 43 Clinically significant bleeding in Mallory-Weiss syndrome is associated with risk factors such as old age, coagulation disorders, underlying diseases such as portal hypertension, and active bleeding during endoscopic examination. Endoscopic hemostasis is necessary even in healthy patients without comorbidities when active bleeding, such as spurting or oozing, is observed during endoscopic examination.…”
Section: Bodymentioning
confidence: 99%
“… 41 , 42 A prospective study found that the 30-day mortality rate in Mallory-Weiss syndrome was 5.3%, similar to the mortality rate in peptic ulcer bleeding. 43 Clinically significant bleeding in Mallory-Weiss syndrome is associated with risk factors such as old age, coagulation disorders, underlying diseases such as portal hypertension, and active bleeding during endoscopic examination. Endoscopic hemostasis is necessary even in healthy patients without comorbidities when active bleeding, such as spurting or oozing, is observed during endoscopic examination.…”
Section: Bodymentioning
confidence: 99%
“…Mallory-Weiss tears (MWTs), characterized by mucosal lacerations in the region of the esophagogastric junction (EGJ), are a common cause of nonvariceal gastrointestinal bleeding. MWTs are usually caused by retching or forceful vomiting, and the reported incidence is as high as 15 % of all cases of acute upper gastrointestinal bleeding 1 2 3 . MWTs have also been recognized as an iatrogenic adverse event occurring during upper gastrointestinal endoscopic procedures, initially documented in 1976 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Massive hemorrhage is a leading cause of mortality . Resuscitation of massive hemorrhage has shifted toward earlier administration of plasma to reduce mortality .…”
mentioning
confidence: 99%